Zinc negative electrode gel electrolyte integrated structure, preparation method thereof and zinc ion battery
By adopting a single-ion conductive dual-network polymer structure in zinc-ion batteries, the problems of polarization effect of electrode concentration and reduced zinc ion desolvation ability caused by anion interference are solved, and the battery cycle performance and service life are improved.
Patent Information
- Application Number
- CN202510037123.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing gel electrolytes have anionic interference in zinc-ion batteries, resulting in electrode concentration polarization effect, reduced zinc ion desolvation ability and short battery cycle life.
The zinc negative electrode gel electrolyte integrated structure adopts a single-ion conductive dual network polymer structure. By in-situ polymerization on the surface of the zinc negative electrode, the zinc ions are fixed on the polymerization chain to prevent the free movement of anions.
It significantly improves the circulation performance and service life of zinc ion batteries, and enhances the ionic conductivity and charge and discharge efficiency of the battery.
Smart Images

Figure BDA0005235842060000091
Abstract
Description
Technical Field
[0001] The embodiments of the present application belong to the technical field of zinc ion batteries, and in particular, relate to an integrated zinc negative electrode gel electrolyte structure and a preparation method thereof, and a zinc ion battery. Background Art
[0002] Gel electrolytes have been widely used in academia and business circles because of their characteristics of being non-leaky, non-flammable, and preventing electrode expansion, which make batteries safer and more stable. At present, commonly used gel electrolytes need to add electrolyte salts as key components to provide ion transport, which inevitably introduces anions, which will have an adverse effect on battery performance: first, the free movement of these anions in the gel electrolyte will increase the possibility of electrode concentration polarization effect; second, these anions will be entangled with zinc ions during the battery cycle, reducing the desolvation ability of zinc ions, which will not only slow down the conversion of zinc ions to zinc, but also may cause side reactions at the zinc negative electrode, thereby affecting the battery's charging and discharging speed and cycle life. In addition, the solid gel electrolyte has poor contact with the electrode interface, which is not conducive to the transmission of electrons and ions between the two, thereby reducing the battery's ionic conductivity. Therefore, it is necessary to provide a gel electrolyte that has no anion interference, high ionic conductivity, and excellent contact with the zinc negative electrode. Summary of the invention
[0003] In view of this, the embodiments of the present application provide an integrated structure of a zinc negative electrode gel electrolyte, a preparation method thereof, and a zinc ion battery. The gel electrolyte in the integrated structure is a single-ion conductive double-network polymer, which has a stable structure and excellent contact properties, so that the battery system has high ionic conductivity. The anions in the system are fixed on the polymer chains, and there are no freely moving anions to interfere with the insertion and extraction of zinc ions, which greatly improves the cycle performance of the zinc ion battery and extends its service life.
[0004] In a first aspect, an embodiment of the present application provides an integrated zinc negative electrode gel electrolyte structure, characterized in that it includes a zinc negative electrode and a gel electrolyte layer in situ bonded to the surface of one side or both sides of the zinc negative electrode; the gel electrolyte layer includes a polymerization product of zinc acrylate monomer, acrylic acid monomer and gel substance; the gel substance includes a gel monomer and / or a gelling agent.
[0005] In the embodiment of the present application, the gel monomer includes one or more of acrylamide, methacryloyloxyethyl dimethylalkyl ammonium bromide, N-isopropyl acrylamide, methacrylic acid, N-vinyl pyrrolidone, vinyl ester hyaluronic acid, N-vinyl imidazole, methylene acrylamide, 2-hydroxyethyl methacrylate, and 2-acrylamido-2-methyl-1-propanesulfonic acid sodium; the gelling agent includes one or more of xanthan gum, gelatin, carrageenan, guar gum, agar, and sodium alginate.
[0006] In the embodiment of the present application, the ionic conductivity of the gel electrolyte layer is 7.5×10 -4 S / cm-6×10 -3 S / cm, thickness is 10μm-50μm.
[0007] In a second aspect, the present application provides a method for preparing an integrated structure of a zinc negative electrode gel electrolyte, characterized in that it comprises the following steps:
[0008] Mixing zinc acrylate monomer, acrylic monomer, gel substance, photoinitiator and cross-linking agent to obtain a mixed raw material liquid, wherein the gel substance includes gel monomer and / or gelling agent;
[0009] The mixed raw material liquid is placed on one side or both sides of the zinc negative electrode surface, and after ultraviolet polymerization, a gel electrolyte layer in situ combined with the surface of the zinc negative electrode is formed to obtain an integrated zinc negative electrode gel electrolyte structure.
[0010] In the embodiment of the present application, in the mixed raw material liquid, the ratio of the mass of the zinc acrylate monomer to the total mass of the acrylic acid monomer and the gel-like substance is (10:90)-(50:50).
[0011] In the embodiment of the present application, the mixing includes: dissolving the zinc acrylate monomer in a first solvent to obtain a first solution, wherein the concentration of the zinc acrylate monomer in the first solution is 0.05 g / mL-0.25 g / mL;
[0012] dissolving an acrylic monomer and a gel monomer in a second solvent to obtain a second solution, wherein the molar ratio of the acrylic monomer to the gel monomer in the second solution is 1:(2-6);
[0013] The first solution, the second solution, the photoinitiator and the cross-linking agent are mixed to obtain a mixed raw material solution.
[0014] In the embodiment of the present application, based on the total molar number of zinc acrylate monomer, acrylic monomer and gel monomer in the mixed raw material liquid, the molar concentration of the photoinitiator is 0.01%-0.05%, and the molar concentration of the crosslinking agent is 0.01%-0.05%.
[0015] In the embodiment of the present application, the UV light intensity of the UV polymerization is 500W / cm2 -1000W / cm 2 , wavelength is 365nm-395nm, time is 30min-90min.
[0016] In the embodiment of the present application, the mixed raw material liquid is further deoxygenated before the ultraviolet polymerization, and the deoxygenation includes introducing 0.1SLPM-1SLPM of nitrogen into the mixed raw material liquid for 30min-60min.
[0017] In a third aspect, an embodiment of the present application further provides a zinc ion battery, comprising a positive electrode and a zinc negative electrode gel electrolyte integrated structure provided in the first aspect of the present application or a zinc negative electrode gel electrolyte integrated structure prepared by the preparation method provided in the second aspect of the present application, wherein one side of the gel electrolyte layer in the zinc negative electrode gel electrolyte integrated structure is arranged close to the positive electrode. DETAILED DESCRIPTION
[0018] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available products.
[0020] Desolvation ability of zinc ions: The ability of zinc ions to separate from their solvation structures (such as water molecules). In this application, it refers to the ability of the bound zinc on the zinc acrylate structural unit on the gel electrolyte polymer chain to be converted into zinc ions during the battery charging and discharging process.
[0021] Battery concentration polarization effect: During the battery charging and discharging process, the accumulation and diffusion rate of ions in the electrolyte on the electrode surface do not match, causing the electrolyte concentration near the electrode to change, thereby forming a concentration gradient that increases the resistance to ion migration.
[0022] UV polymerization: UV irradiation triggers the photoinitiator to generate free radicals or cations, which in turn triggers monomer polymerization, cross-linking and branching chemical reactions, converting the material from liquid to solid. In this application, it refers to the formation of a polymer gel electrolyte layer by UV polymerization of the mixed raw material liquid.
[0023] In-situ polymerization: All reactive monomers and catalysts are added to the continuous phase. Since the monomers are soluble in the continuous phase, but the polymers are insoluble in the entire system, the polymerization reaction occurs on the continuous phase core material. As the reaction proceeds, the monomers are prepolymerized, and then the prepolymers are polymerized. When the size of the prepolymers gradually increases, they will be deposited on the surface of the core material.
[0024] Oxygen inhibition: During the UV curing process, the photoinitiator generates free radicals after absorbing UV light, and these free radicals bond with each monomer molecule to form a continuous polymer chain. However, oxygen molecules in the air will intervene in this process, causing the "oxygen inhibition" phenomenon, which will cause the free radicals to be quenched or weakened by oxygen, thereby reducing the overall concentration of free radicals and affecting the completeness of the polymerization reaction.
[0025] Gelling agent: An external substance that can transform a liquid or semi-fluid into a uniform semi-rigid solid and maintain its original shape. Its mechanism of action is to fix the dispersed medium in the structure by forming a network structure. In this application, it refers to adhesive gums such as xanthan gum, gelatin, carrageenan, guar gum, agar, sodium alginate, etc.
[0026] Ion mobility number: defined as the ratio of the charge transferred by a certain ion to the total charge, with a value between 0 and 1, reflecting the ability of ions to migrate charges in an electric field.
[0027] Aqueous zinc-ion batteries have aqueous electrolytes, which avoid the safety hazards of traditional batteries such as flammability and explosion caused by organic phase electrolytes. They also have high theoretical capacity and low cost, making them stand out in large-scale electrochemical energy storage systems. However, aqueous electrolytes still have undesirable phenomena such as easy leakage, zinc dendrites, and side reactions during battery cycles. At present, technical personnel in the industry are mainly working on solving the problem of zinc negative electrodes from the aspects of zinc electrode structure design, zinc electrode surface protective layer design, and the use of gel electrolytes instead of electrolytes and diaphragms. Among them, gel electrolytes have the characteristics of being difficult to leak, difficult to ignite and explode, and can prevent electrode expansion, making the battery both safe and stable, and have received widespread attention and application in academia and the business community. Gel electrolytes need to add zinc electrolyte salts as a key component to provide ion transport, and anions are inevitably introduced at this time, which has an adverse effect on the battery cycle: on the one hand, these anions move freely in the gel electrolyte, and the anions often accumulate on the electrode surface and the diffusion rate does not match, which increases the possibility of electrode concentration polarization effect; on the other hand, these anions combine or entangle with zinc ions during the battery cycle, which increases the difficulty of zinc ion desolvation, which not only slows down the conversion of zinc ions to zinc, but also causes side reactions at the zinc electrode, thereby affecting the battery's charging and discharging speed and cycle life. In addition, the solid gel electrolyte has poor contact with the electrode interface, and the assembled structure is not firm, which is not conducive to the transmission of electrons and ions between the two, thereby reducing the ionic conductivity. Therefore, it is necessary to provide a gel electrolyte that is free of anion interference, has high ionic conductivity, and has excellent contact with the zinc negative electrode.
[0028] In view of this, the embodiment of the present application provides an integrated structure of a zinc negative electrode gel electrolyte, a preparation method thereof, and a zinc ion battery. The preparation method includes using zinc acrylate as a zinc electrolyte salt, and jointly generating a gel electrolyte layer on the surface of the zinc negative electrode through a UV polymerization reaction with an acrylic monomer and a gel substance under the action of a photoinitiator and a cross-linking agent. The gel electrolyte layer has a single-ion conductive double-network polymer structure, and has the advantages of no anion interference, high ionic conductivity, and excellent contact with the zinc negative electrode. The preparation method is simple, easy, low-cost, environmentally friendly, and suitable for industrial production.
[0029] The present application provides a zinc negative electrode gel electrolyte integrated structure, comprising a zinc negative electrode and a gel electrolyte layer in-situ bonded to the surface of one side or both sides of the zinc negative electrode, the gel electrolyte layer comprising a polymerization product of a zinc acrylate monomer, an acrylic acid monomer and a gel-like substance, and the gel-like substance comprises a gel-like monomer and / or a gelling agent.
[0030] In the zinc negative electrode gel electrolyte integrated structure provided by the present application, the gel electrolyte layer is a single ion conductive double network polymer, in which zinc acrylate is fixed on the polymer chain as an electrolyte salt, so there are no free anions in the system, avoiding the battery concentration polarization effect caused by anion interference, and enhancing the desolvation ability of zinc ions. Compared with the traditional assembly form, the integrated structure is firm and stable, significantly improving the contact between the gel electrolyte layer and the zinc negative electrode, thereby enhancing the ionic conductivity of the system.
[0031] In some embodiments of the present application, the gel-like substance is a gel-like monomer, such as but not limited to acrylamide, methacryloyloxyethyl dimethyl alkyl ammonium bromide, N-isopropyl acrylamide, methacrylic acid, N-vinyl pyrrolidone, vinyl ester hyaluronic acid, N-vinyl imidazole, methylene acrylamide, 2-hydroxyethyl methacrylate, 2-acrylamido-2-methyl-1-propanesulfonic acid sodium or more. In some embodiments of the present application, the gel electrolyte layer mainly relies on the interaction force between the gel-like monomer molecules to form a physical cross-linked structure, so that it presents a gel state.
[0032] In some other embodiments of the present application, the gel-like substance is a gelling agent, such as but not limited to one or more of xanthan gum, gelatin, carrageenan, guar gum, agar, and sodium alginate. First, the gelling agent itself has physical adhesion, and it combines with polymers formed by polymerization of other monomers to form a conductive double network gel electrolyte layer with strong interactions in which the physical network and the chemical network are mutually interpenetrated; secondly, the gelling agent usually has excellent thermal stability, which can enable the gel electrolyte layer to maintain its physical and chemical properties in a higher temperature environment of battery heat release; in addition, the gelling agent in the gel electrolyte layer can also promote the uniform nucleation of zinc and reduce the formation of dendritic zinc dendrites.
[0033] In the embodiment of the present application, the ionic conductivity of the zinc negative electrode gel electrolyte integrated structure is 7.5×10 -4 S / cm-6×10 -3 S / cm.
[0034] In the embodiment of the present application, the thickness of the gel electrolyte layer is 10μm-50μm, for example, it can be but not limited to 10μm, 20μm, 30μm, 40μm, 50μm, this thickness depends on the formula composition of the mixed raw material solution in the preparation method below, the coating thickness and the joint control of the ultraviolet polymerization process. Too thin thickness may lead to insufficient mechanical strength of the gel electrolyte layer, and the battery is more prone to short circuit. Too thick thickness will extend the ion transmission path, increase the internal resistance of the battery, and reduce the energy density and charge and discharge efficiency of the battery. The embodiment of the present application controls the thickness of the gel electrolyte layer between 10μm-50μm, which not only ensures its mechanical strength, but also takes into account the ion conduction efficiency, thereby optimizing the physical and chemical performance of the battery.
[0035] First, the gel electrolyte layer provided by the present application has a single-ion conductive double-network polymer structure, wherein the first network is a physical cross-linked network formed by connecting the gel-like substance through intermolecular interaction forces, and the second network is a polymer molecule chain formed by connecting the gel-like substance, zinc acrylate monomer and acrylic monomer through chemical bonds, i.e., a chemical cross-linked network, and the two networks penetrate and entangle with each other to form a conductive double-network gel electrolyte with strong interaction. Traditional gel electrolytes use zinc salts or other metal salts as electrolyte salts, and the anions introduced with the zinc salts are free in the system, which may cause electrode concentration polarization effects. These anions will also entangle with zinc ions and affect the insertion and extraction of zinc ions during charging and discharging, which inevitably reduces the desolvation ability of zinc ions. The gel electrolyte layer provided in the present application uses zinc acrylate as the electrolyte salt, which undergoes a polymerization reaction with other monomers or substances and is fixed on the polymer chain. Therefore, there are no free, freely movable anions in the system, and the zinc ions are only connected to or detached from the polymer chain, which greatly increases the zinc ion migration number. Only the zinc ions move and transform in the system, so that the single-ion conductive double-network polymer gel electrolyte layer has the advantages of no anion interference, high ionic conductivity, etc.
[0036] Secondly, the gel electrolyte layer provided in the present application is formed by in-situ polymerization of a mixed raw material liquid on the surface of a zinc negative electrode, wherein the mixed raw material liquid includes a zinc acrylate monomer, an acrylic monomer, and a gel-like substance. During the in-situ polymerization process, the mixed raw material liquid can well infiltrate the zinc negative electrode, and the zinc acrylate therein can also improve the binding force with the base zinc negative electrode, forming a closer interface contact, thereby reducing the interface resistance between the gel electrolyte layer and the zinc negative electrode. The zinc negative electrode gel electrolyte integrated structure overcomes the problems of poor contact between the gel electrolyte and the electrode interface and looseness after assembly in the prior art, thereby reducing the interface impedance, improving the zinc ion transmission flux at the interface, and further enhancing the ionic conductivity and the energy density of the battery.
[0037] In summary, the integrated structure of the zinc negative electrode gel electrolyte provided in the present application has a single-ion conductive dual network system, which provides a developed transmission path for the ion transmission and electron movement of the battery. There are no free anions in the system to interfere with the desolvation of zinc ions or induce battery polarization effects. The gel electrolyte and the zinc negative electrode are integrally formed, and the two have good contact and interface compatibility, which helps to increase the migration number of zinc ions in the system, thereby improving the ionic conductivity of the battery and extending the cycle life of the battery.
[0038] The present invention provides a method for preparing a zinc negative electrode gel electrolyte integrated structure, comprising the following steps:
[0039] S101, mixing zinc acrylate monomer, acrylic monomer, gel substance, photoinitiator and cross-linking agent to obtain a mixed raw material liquid, wherein the gel substance includes gel monomer and / or gelling agent;
[0040] S102, placing the mixed raw material liquid on one side or both sides of the zinc negative electrode surface, forming a gel electrolyte layer in situ bonded to the surface of the zinc negative electrode after ultraviolet polymerization, and obtaining an integrated zinc negative electrode gel electrolyte structure.
[0041] The preparation method provided by the present application sets a mixed raw material liquid containing zinc acrylate monomer, acrylic monomer, gel substance, photoinitiator and cross-linking agent on one side or both sides of the zinc negative electrode surface, and uses ultraviolet polymerization to form a gel electrolyte layer in situ combined with the surface of the zinc negative electrode to obtain a zinc negative electrode gel electrolyte integrated structure. The preparation method is simple, easy to operate, low-cost, environmentally friendly, and suitable for industrial production.
[0042] In step S101, in the mixed raw material liquid, the ratio of the mass of zinc acrylate monomer to the total mass of acrylic monomer and gel-like substance is (10:90)-(50:50), for example, it can be but not limited to 10:90, 20:80, 30:70, 40:60, 50:50. In some embodiments of the present application, the ratio of the mass of zinc acrylate monomer to the total mass of acrylic monomer and gel-like substance is (35:65)-(45:55). The content of gel-like substance directly affects the degree of curing, hardness and stability of the physical cross-linked network in the gel electrolyte layer. Zinc acrylate monomer and acrylic monomer are connected by chemical bonds to form a chemical cross-linked network in the gel electrolyte. The appropriate content of zinc acrylate monomer can ensure that sufficient zinc ion source is provided for battery circulation, while avoiding excessive zinc acrylate monomer causing it to agglomerate and form ion clusters, affecting the uniformity and conductivity of the polymer network finally formed. The ratio of the three directly determines the mechanical properties and chemical properties of the conductive double network gel electrolyte layer finally formed.
[0043] In the embodiments of the present application, the acrylic monomer includes but is not limited to one or more of acrylic acid, methyl acrylate, ethyl acrylate, and n-butyl acrylate. In some embodiments of the present application, the acrylic monomer is acrylic acid, which can polymerize with other monomers to form a polymer conductive network and also promotes the solubility of the zinc acrylate monomer in the mixed raw material solution.
[0044] In some embodiments of the present application, the gel-like substance is a gel-like monomer, as described above, which will not be repeated here. In some specific embodiments of the present application, the gel-like monomer is acrylamide.
[0045] In other embodiments of the present application, the gel-like substance is a gelling agent, as described above, and will not be repeated here. In the embodiments of the present application, the molecular weight of the gelling agent is 200Mw-10000Mw, for example, it can be but not limited to 200Mw, 500Mw, 1000Mw, 2000Mw, 3000Mw, 4000Mw, 5000Mw, 6000Mw, 7000Mw, 8000Mw, 9000Mw, 10000Mw; the mass percentage (or volume percentage) of the gelling agent in the mixed raw material liquid is 10%-50%, for example, it can be but not limited to 10%, 20%, 30%, 40%, 50%. Adding a gelling agent with a suitable molecular weight and content can ensure that the volume, viscosity, swelling and mechanical strength of the gel electrolyte layer finally formed are controlled without affecting the movement of ions, which is of great significance for preventing electrolyte consumption and battery expansion.
[0046] In the embodiment of the present application, the mixing form of the substances in the mixed raw material liquid includes: dissolving zinc acrylate monomer in a first solvent to obtain a first solution, dissolving acrylic monomer and gel monomer in a second solvent to obtain a second solution, and then mixing the first solution, the second solution, a photoinitiator and a cross-linking agent to obtain a mixed raw material liquid.
[0047] In the embodiment of the present application, the concentration of zinc acrylate monomer in the first solution is 0.05g / mL-0.25g / mL, for example, it can be but not limited to 0.05g / mL, 0.08g / mL, 0.1g / mL, 0.12g / mL, 0.15g / mL, 0.2g / mL, 0.22g / mL, 0.25g / mL. In some specific embodiments of the present application, the concentration of zinc acrylate monomer in the first solution is 0.18g / mL-0.22g / mL. The appropriate concentration of zinc acrylate in the first solution provides sufficient zinc ion source for the gel electrolyte prepared subsequently, while avoiding its excessive content to agglomerate to form ion clusters, thereby hindering the zinc ion transmission during battery cycling.
[0048] In the embodiments of the present application, the first solvent is an organic solvent, including one of a halogenated hydrocarbon solvent, an alcohol solvent, a ketone solvent, and an aromatic hydrocarbon solvent. In some embodiments of the present application, the first solvent may be, for example, but not limited to, one or more of 2-methoxyethanol, dichloromethane, bromopropane, trichloroethane, and acetone. The first solvent is used to dissolve zinc acrylate. In addition, the gel electrolyte layer contains an appropriate amount of organic solvent, which can also provide an ion transmission channel and environment for battery circulation, and can also adjust the pore size and porosity of the polymer, which helps to improve the ionic conductivity and stability of the gel electrolyte layer.
[0049] In an embodiment of the present application, the molar ratio of acrylic monomer to gel monomer in the second solution is 1:(:2-6), for example, it can be but not limited to 1:2, 1:3, 1:4, 1:5, 1:6. In some embodiments of the present application, the molar ratio of acrylic monomer to gel monomer in the second solution is 1:(4-6). Acrylic monomer and zinc acrylate monomer are chemically bonded to form a chemical cross-linked network in the gel electrolyte layer. The content of gel monomer directly affects the mechanical properties of the physical cross-linked network in the gel electrolyte layer, including the degree of curing, hardness and stability, etc. Therefore, the ratio of acrylic monomer to gel monomer determines the ratio of the physical cross-linked network and the chemical cross-linked network in the gel electrolyte layer to a great extent. The appropriate molar ratio of the two is helpful to coordinate the physical and chemical properties of the gel electrolyte layer.
[0050] In the embodiment of the present application, the second solvent may be, for example, but not limited to, one or more of water, methanol, and ethanol. The total molar concentration of acrylic monomers and gel monomers in the second solution is 5 mol / L-10 mol / L, for example, but not limited to 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L. The second solvent needs to have good solubility for both acrylic monomers and gel monomers. An appropriate amount of the second solvent can promote the dissolution and diffusion of the monomers, help the mutual contact between the monomers, and avoid excessive dilution of the concentration of the reactants, so that the polymerization reaction has a suitable reaction rate and conversion rate.
[0051] In the embodiment of the present application, the photoinitiator may be, for example, but not limited to, one or more of Lencolo 5050W, 2,2-dimethoxyphenylacetophenone, acrylcarboxylic acid diester, photoinitiator 1173, photoinitiator 184, photoinitiator 907, benzaldehyde-formaldehyde trimer, ketoamine photoinitiator, and azole aniline photoinitiator. Based on the total molar number of zinc acrylate monomer, acrylic monomer, and gel monomer in the mixed raw material liquid, the molar concentration of the photoinitiator is 0.01%-0.05%, for example, but not limited to 0.01%, 0.02%, 0.03%, 0.04%, and 0.05%. The photoinitiator is a key component of the UV curing system and is used to initiate the polymerization reaction of the prepolymer. Controlling its addition amount helps to accelerate the curing speed of the gel electrolyte layer, while avoiding the extension of the curing time due to excessive use, increasing the time cost and raw material cost, and may also trigger the side reaction of the photoinitiator itself.
[0052] In the embodiment of the present application, the crosslinking agent may be, for example, but not limited to, one or more of N,N'-methylenebisacrylamide, organic peroxide crosslinking agent, carboxylic acid and anhydride crosslinking agent, and amine crosslinking agent. Based on the total molar number of zinc acrylate monomer, acrylic monomer, and gel monomer in the mixed raw material liquid, the molar concentration of the crosslinking agent is 0.01%-0.05%, for example, but not limited to 0.01%, 0.02%, 0.03%, 0.04%, 0.05%. The crosslinking agent forms a network structure by generating chemical bonds between the monomer molecules, thereby significantly improving the strength and elasticity of the material, so that the formed gel electrolyte layer has suitable physical and chemical properties. Controlling the amount of crosslinking agent added is beneficial to improving the heat resistance, corrosion resistance, and aging resistance of the gel electrolyte layer, while avoiding excessive use to increase the brittleness of the gel electrolyte, causing it to crack or break, thereby reducing the adhesion between the gel electrolyte layer and the zinc negative electrode, resulting in separation of the two.
[0053] In step S102, before the mixed raw material liquid is arranged on the surface of the zinc negative electrode, the mixed raw material liquid is also deoxygenated, and the specific operation includes introducing a non-reactive gas into the mixed raw material liquid, such as but not limited to nitrogen and / or argon, and its volume flow rate is 0.1SLPM-1SLPM, such as but not limited to 0.1SLPM, 0.3SLPM, 0.5SLPM, 0.8SLPM, 1SLPM; the deoxygenation time is 30min-60min, such as but not limited to 30min, 35min, 40min, 45min, 50min, 55min, 60min. Oxygen molecules in the environment will intervene in the ultraviolet polymerization process, causing the "oxygen inhibition" phenomenon, thereby affecting the completeness of the polymerization reaction, or causing the surface of the zinc negative electrode to become sticky, sticky or greasy. Based on this, the present application removes oxygen in the mixed raw material liquid before ultraviolet polymerization, which can effectively avoid the "oxygen inhibition" phenomenon, which is conducive to ensuring the quality of the integrated structure of the zinc negative electrode gel electrolyte.
[0054] In the embodiment of the present application, the mixed raw material liquid is arranged on the surface of the zinc negative electrode in the form of single-side coverage, double-side coverage or full coverage. The thickness of the coating formed by the mixed raw material liquid on the surface of the zinc negative electrode is 20μm-80μm, for example, but not limited to 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm. The coating has a suitable thickness on the one hand to obtain a gel electrolyte layer of a preset thickness, and on the other hand to reduce the chance of oxygen entering the coating, which can also reduce the possibility of "oxygen inhibition" to a certain extent.
[0055] In the embodiment of the present application, the UV polymerization includes placing the zinc negative electrode with the mixed raw material liquid on the surface 10cm-15cm away from the UV light source for continuous irradiation, and the UV light intensity is 500W / cm 2 -1000W / cm 2 , for example but not limited to 500W / cm 2 、600W / cm 2 , 700W / cm 2 , 800W / cm 2 , 900W / cm 2 , 1000W / cm 2. The intensity of ultraviolet light directly affects the activation efficiency of the photoinitiator. Appropriate ultraviolet light intensity can accelerate the activation of the photoinitiator and promote the polymerization reaction of the monomer faster, while avoiding excessive light intensity causing local overheating and affecting the uniformity of the curing of the gel electrolyte layer; the wavelength of ultraviolet light is 365nm-395nm, for example, it can be but not limited to 365nm, 370nm, 375nm, 380nm, 385nm, 390nm. After repeated experiments, the wavelength of ultraviolet light in this range is adapted to the photosensitivity of the gel electrolyte polymer provided in this application; the time of ultraviolet light irradiation is 30min-90min, for example, it can be but not limited to 30min, 40min, 50min, 60min, 70min, 80min, 90min. First, this illumination duration can ensure that the zinc acrylate monomer bonds with other monomers to form a stable cross-linked conductive network, which can effectively avoid problems such as incomplete curing due to insufficient light, resulting in shedding / cracking, or excessive cross-linking of materials due to long-term illumination; secondly, too much solvent will affect the curing degree of the gel electrolyte, and too little solvent will reduce the solubility of the polymer and cause gel precipitation. The appropriate UV irradiation duration helps to remove some organic solvents in the system, thereby ensuring the structural uniformity and mechanical strength of the gel electrolyte layer.
[0056] In the embodiment of the present application, the zinc acrylate monomer, the acrylic monomer and the gel-like substance are soluble in the mixed raw material liquid, and the polymer formed after the ultraviolet polymerization is insoluble in the system, so the ultraviolet polymerization reaction will occur on the zinc negative electrode, each monomer will be prepolymerized, and the prepolymer will be polymerized again. When the polymerization size of the prepolymer gradually increases, it will be deposited on the surface of the base zinc negative electrode. At the same time, the carboxyl groups in the zinc acrylate structural unit and the acrylic structural unit in the polymer can form coordination bonds with the zinc negative electrode, further strengthening the binding force between the gel electrolyte polymer and the base zinc negative electrode, thereby forming an integrated structure of the zinc negative electrode gel electrolyte.
[0057] The preparation process of the integrated structure of zinc negative electrode gel electrolyte provided in the present application is carried out at room temperature.
[0058] In the preparation method of the integrated structure of zinc negative electrode gel electrolyte provided in the embodiment of the present application, the formula composition of the mixed raw material liquid and the ultraviolet in-situ polymerization process take into account the curing effect, product quality, production cost and environmental protection of the gel electrolyte layer. Compared with the traditional non-in-situ polymerization method, this preparation method is simpler and compatible with existing commercial battery production. It can simplify the preparation process, reduce costs, and is suitable for industrial production.
[0059] An embodiment of the present application also provides a zinc ion battery, which includes a positive electrode and a zinc negative electrode gel electrolyte integrated structure as described above in the present application or a zinc negative electrode gel electrolyte integrated structure prepared by the preparation method as described above in the present application, wherein one side of the gel electrolyte layer in the integrated structure is arranged close to the positive electrode.
[0060] In the embodiment of the present application, the positive electrode may be, for example but not limited to, one of oxide materials, carbon materials, zinc materials, vanadium-based materials, and composite materials of oxides and carbon materials.
[0061] In the embodiment of the present application, the gel electrolyte in the zinc ion battery can completely avoid a series of safety problems caused by electrolyte leakage compared to the electrolyte solution of the conventional aqueous battery. In addition, the integrated structure of the gel electrolyte and the zinc negative electrode, compared with the assembly method of the prior art in which the gel electrolyte and the zinc negative electrode are closely attached, the integrated structure guarantees the contact between the two to the greatest extent, and also improves the firmness and stability of the battery structure. Its own solid properties can prevent the positive and negative electrodes of the battery from contacting, so there is no need to set up an additional diaphragm, thereby simplifying the assembly procedure of the battery and extending the service life of the battery. And its preparation process and the final product have good environmental friendliness, and it will become a mainstream zinc ion battery with broad application prospects in the future.
[0062] The zinc ion battery provided in this application can be used in energy storage, emergency power supply and other fields. Since the gel electrolyte has high toughness, stretchability, rapid repairability and safety, the zinc ion battery is more suitable for flexible and wearable electronic devices and portable electronic products.
[0063] The technical solution of the present application is further described below with multiple embodiments.
[0064] Example 1
[0065] (1) Under room temperature, zinc acrylate monomer is dissolved in 2-methoxyethanol solvent to obtain a first solution with a concentration of 0.2 g / mL; at the same time, acrylic acid monomer and acrylamide monomer are dissolved in water at a molar ratio of 1:5 to obtain a second solution with a total concentration of 8 mol / L; the first solution and the second solution are mixed, and the ratio of the mass of zinc acrylate monomer to the total mass of acrylamide monomer and acrylic acid monomer in the mixed solution is 40:60.
[0066] (2) Based on the total molar number of zinc acrylate monomer, acrylamide monomer and acrylic acid monomer, add 0.05% of a photoinitiator (Lencolo 5050W) and 0.01% of a N,N'-methylenebisacrylamide cross-linking agent to the mixed solution, stir evenly, and obtain a mixed raw material liquid; then continuously introduce 0.5 SLPM of nitrogen into the mixed raw material liquid for deoxygenation, and stop deoxygenation after 45 minutes.
[0067] (3) Pour the deoxygenated mixed raw material liquid onto the surface of the zinc negative electrode sheet and the peelable substrate respectively, place them 12 cm away from the UV polymerization lamp, and set the UV light intensity to 800 W / cm 2 , the wavelength is 365nm, and after continuous irradiation for 60min, an integrated structure of zinc negative electrode gel electrolyte and a separate gel electrolyte layer were obtained. The thickness of the gel electrolyte layers of both were 20μm.
[0068] Example 2
[0069] The only difference from Example 1 is that in the mixed raw material liquid, the ratio of the mass of the zinc acrylate monomer to the total mass of the acrylamide monomer and the acrylic acid monomer is 50:50.
[0070] Example 3
[0071] The only difference from Example 1 is that in the mixed raw material liquid, the ratio of the mass of the zinc acrylate monomer to the total mass of the acrylamide monomer and the acrylic acid monomer is 20:80.
[0072] Example 4
[0073] The only difference from Example 1 is that in the mixed raw material liquid, the ratio of the mass of zinc acrylate monomer to the total mass of acrylamide monomer and acrylic acid monomer is 10:90.
[0074] Example 5
[0075] The only difference from Example 1 is that the concentration of the zinc acrylate monomer in the first solution is 0.25 g / mL.
[0076] Comparative Example 1
[0077] The only difference from Example 1 is that zinc acrylate monomer is not introduced into the system.
[0078] Comparative Example 2
[0079] The only difference from Example 1 is that zinc sulfate is used to replace the zinc acrylate monomer.
[0080] Comparative Example 3:
[0081] The only difference from Example 1 is that the mixed raw material liquid is not disposed on the zinc negative electrode, and it polymerizes on the polytetrafluoroethylene mold to form a gel electrolyte, and does not form an integrated structure with the zinc negative electrode.
[0082] The ionic conductivity of the gel electrolyte layer prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 was detected: the gel electrolyte layer was placed between two stainless steel sheets, assembled into a button cell, and an AC impedance spectroscopy test was performed using a Chenhua electrochemical workstation CHI660E to detect the ionic conductivity.
[0083] The zinc negative electrode gel electrolyte integrated structures prepared in Examples 1-5 and Comparative Examples 1-3 were respectively assembled into zinc-zinc symmetric batteries, and a constant voltage of 10 mV was applied using a Chenhua electrochemical workstation CHI660E, and the zinc ion migration number was detected by constant potential polarization method.
[0084] The zinc negative electrode gel electrolyte integrated structures prepared in Examples 1-5 and Comparative Examples 1-3 were respectively assembled into zinc-zinc symmetrical batteries, and the current density was set to 10 mA / cm 2 , capacity is 15mAh / cm 2 , continuously cycle charge and discharge for 30 minutes until the battery fails, and record the cycle failure time of each battery.
[0085] The test results of ionic conductivity, zinc ion migration number and battery cycle performance of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1:
[0086] Table 1 Test results of Examples 1-5 and Comparative Examples 1-3
[0087]
[0088] The industry usually defines ionic conductivity as less than 3.0×10 -4 S / cm gel electrolyte is considered as unusable gel electrolyte. From the test results in Table 1, it can be seen that the ionic conductivity of the gel electrolyte layer prepared in Examples 1-5 is far more than 3.0×10 -4 S / cm.
[0089] In Examples 1-5, an appropriate concentration of zinc acrylate monomer is introduced into the mixed raw material liquid, and the ratio of the mass of the zinc acrylate monomer to the total mass of the acrylamide monomer and the acrylic acid monomer is controlled within an appropriate range. When the zinc negative electrode gel electrolyte integrated structure prepared in this way is assembled into a battery with the positive electrode, the cycle failure time of the battery under continuous cycle charge and discharge is more than 1000h, which is 2-3 times longer than that of Comparative Example 2.
[0090] The difference between Examples 2-4 and Example 1 is only that the mass ratio of zinc acrylate monomer to the other two monomers in the mixed raw material solution is different. From the results in Table 1, it can be seen that within the range of (10:90)-(40:60), if the proportion of zinc acrylate monomer in the mixed raw material solution is larger, the number of zinc ions that can be provided by the system is larger, which is more conducive to improving the migration speed and migration number of zinc ions when the battery is working, so the ion conductivity of Example 1 is significantly higher than that of Example 3 and Example 4; when the proportion of zinc acrylate monomer in the mixed raw material solution is higher than 40%, the lower the concentration of zinc acrylate in the control system, the more conducive it is to avoid the occurrence of agglomeration to form ion clusters and hinder ion migration, so the ion conductivity and ion migration number of Example 1 are higher than those of Example 2. Therefore, when the ratio of the mass of zinc acrylate monomer in the mixed raw material solution to the total mass of acrylic monomer and gel-like substance is (35:65)-(45:55), the obtained zinc negative electrode gel electrolyte integrated structure has the best performance.
[0091] The only difference between Example 5 and Example 1 is that the concentration of zinc acrylate monomer in the first solution of Example 5 is higher, and the higher ionic conductivity of Example 1 is also because it reduces the possibility of agglomeration of zinc acrylate monomer to a certain extent, which is more conducive to ion migration in the system.
[0092] Comparative Example 1 does not introduce zinc acrylate monomer, and there is no zinc ion available for migration in the system. Its ionic conductivity is 10 -15 Order of magnitude, cannot be used as a gel electrolyte for batteries.
[0093] The difference between Comparative Example 2 and Example 1 is that zinc sulfate is used instead of zinc acrylate monomer as the electrolyte salt, and a mobile anion (SO4 2- ), resulting in its zinc ion migration number and battery cycle failure time being significantly lower than those in Example 1, which proves that the gel electrolyte prepared by the polymerization reaction using zinc acrylate as the electrolyte salt provided in the present application is of great significance for improving the zinc ion desolvation ability and zinc ion migration number and extending the battery life.
[0094] The only difference between Comparative Example 3 and Example 1 is that the gel electrolyte is polymerized separately on other removable substrates and does not form an integrated structure with the zinc negative electrode. Compared with Example 1, the interface resistance between the zinc negative electrode and the gel electrolyte of the battery assembled in Comparative Example 3 is increased, resulting in various performances being inferior to those in Example 1, which proves the advantage of the in-situ polymerization scheme provided in the present application.
[0095] The preparation method of the zinc negative electrode gel electrolyte integrated structure provided in the embodiment of the present application designs the formula composition of the mixed raw material liquid and its specific component ratio, and combines it with the preparation process of ultraviolet in-situ polymerization. The preparation method takes into account the curing effect, product quality, production cost and environmental protection of the gel electrolyte layer. Compared with the gel electrolyte prepared by the traditional non-in-situ polymerization method, the zinc negative electrode gel electrolyte integrated structure provided by the present application has higher ionic conductivity. When this integrated structure is assembled into a battery, it can effectively improve the battery's charge and discharge efficiency and significantly extend the battery's cycle life.
[0096] The above disclosure is only the preferred embodiment of the present application, and cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and making equivalent changes according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A zinc negative electrode gel electrolyte integrated structure, characterized in that: The invention comprises a zinc negative electrode and a gel electrolyte layer in-situ bonded to one side or both sides of the zinc negative electrode; the gel electrolyte layer comprises a polymerization product of zinc acrylate monomer, acrylic acid monomer and gel substance; the gel substance comprises gel monomer and / or gelling agent.
2. The zinc negative electrode gel electrolyte integrated structure according to claim 1, characterized in that: The gel monomers include one or more of acrylamide, methacryloyloxyethyl dimethylalkyl ammonium bromide, N-isopropyl acrylamide, methacrylic acid, N-vinyl pyrrolidone, vinyl ester hyaluronic acid, N-vinylimidazole, methylene acrylamide, 2-hydroxyethyl methacrylate, and 2-acrylamido-2-methyl-1-propanesulfonic acid sodium; the gelling agent includes one or more of xanthan gum, gelatin, carrageenan, guar gum, agar, and sodium alginate.
3. The zinc negative electrode gel electrolyte integrated structure according to claim 1, characterized in that: The ionic conductivity of the gel electrolyte layer is 7.5×10 -4 S / cm-6×10 -3 S / cm, thickness is 10μm-50μm.
4. A method for preparing an integrated structure of a zinc negative electrode gel electrolyte, characterized in that: The following steps are involved: Mixing zinc acrylate monomer, acrylic monomer, gel substance, photoinitiator and cross-linking agent to obtain a mixed raw material liquid, wherein the gel substance includes gel monomer and / or gelling agent; The mixed raw material liquid is arranged on one side or both sides of the surface of the zinc negative electrode, and after ultraviolet polymerization, a gel electrolyte layer in situ combined with the surface of the zinc negative electrode is formed to obtain a zinc negative electrode gel electrolyte integrated structure.
5. The method for preparing the integrated structure of zinc negative electrode gel electrolyte according to claim 4, characterized in that: In the mixed raw material liquid, the ratio of the mass of the zinc acrylate monomer to the total mass of the acrylic acid monomer and the gel-like substance is (10:90)-(50:50).
6. The method for preparing the integrated structure of zinc negative electrode gel electrolyte according to claim 4, characterized in that: The mixing includes: Dissolving the zinc acrylate monomer in a first solvent to obtain a first solution, wherein the concentration of the zinc acrylate monomer in the first solution is 0.05 g / mL-0.25 g / mL; dissolving the acrylic monomer and the gel monomer in a second solvent to obtain a second solution, wherein the molar ratio of the acrylic monomer to the gel monomer in the second solution is 1:(2-6); The first solution, the second solution, the photoinitiator and the cross-linking agent are mixed to obtain the mixed raw material solution.
7. The method for preparing the integrated structure of zinc negative electrode gel electrolyte according to claim 4, characterized in that: Based on the total molar number of the zinc acrylate monomer, the acrylic monomer and the gel monomer in the mixed raw material liquid, the molar concentration of the photoinitiator is 0.01%-0.05%, and the molar concentration of the crosslinking agent is 0.01%-0.05%.
8. The method for preparing the integrated structure of zinc negative electrode gel electrolyte according to claim 4, characterized in that: The UV intensity of the UV polymerization is 500 W / cm 2 -1000W / cm 2 , wavelength is 365nm-395nm, time is 30min-90min.
9. The method for preparing the integrated structure of zinc negative electrode gel electrolyte according to claim 4, characterized in that: Before the ultraviolet polymerization, the mixed raw material liquid is further deoxygenated, and the deoxygenation includes introducing 0.1SLPM-1SLPM of nitrogen into the mixed raw material liquid for 30min-60min.
10. A zinc ion battery, characterized in that: It comprises a positive electrode and a zinc negative electrode gel electrolyte integrated structure as described in any one of claims 1 to 3 or a zinc negative electrode gel electrolyte integrated structure prepared by the preparation method as described in any one of claims 4 to 9, wherein one side of the gel electrolyte layer in the zinc negative electrode gel electrolyte integrated structure is arranged close to the positive electrode.
Citation Information
Cited By
Supramolecular gel electrolyte, preparation method thereof and zinc ion battery
CN120767439A
Preparation method of zinc negative electrode of in-situ coupling hydrogel electrolyte and application of zinc negative electrode in zinc battery
CN122025524A
Hierarchical pore double-crosslinking single-ion gel polyelectrolyte, preparation method and application thereof, and aqueous zinc metal battery
CN122127549A
Hydrogel electrolyte with ion migration regulation and control function as well as preparation method and application of hydrogel electrolyte
CN122291723A